Design of wearable squat booster for automobile assembler based on ergonomics. (November 2020) - Chen, Zhewen; Qiao, Zhifeng; Bao, Tianxu; Dou, Fuchao; Chen, Xinpu
Abstract: Aiming at the problem that automobile assembler need to squat for a long time, a wearable squatting assistance system with low cost, simple control and easy to squat and walk is designed. Based on ergonomics and finite element theory, UG was used to draw a three-dimensional solid model of the wearable squatting power system for automobile assemblers. With the help of ANSYS software, the statics analysis of key components is carried out to check their strength and stiffness. It is concluded that the wearable squatting power assist device for automotive fitters based on ergonomics has reached the design requirements in terms of function use and strength and stiffness.